THE MAIN FEATURES OF INTELLIGENT TECHNOLOGIES IN DEVELOPING COUNTRY - Kadirov , Ulug‘bek Ravshanovich; Umaraliev , Asliddin Fakhritdin o‘g‘li (Educational Research in Universal Sciences, 2024)
In the context of Global changes, the economy of our country today is the digital economy that motivates the development and the one that is associated with it how many effective technologies are rapidly entering our lives.